Останній голова Чернігівської губернської земської управи О.О.Свєчин - Рахно, О. (Сiверянський лiтопис, 2009)
Стаття присвячена аналізу життєвого шляху та громадсько-політичної діяльності голови Чернігівської губернської земської управи у 1901-1906 та 1917 - 1918 рр. О.Свєчина. Визначено основі віхи життєвого шляху, схарактеризовано його роботу у губернському земстві та громадсько-політичну діяльність на початку ХХ ст. Статья посвящена анализу жизненного пути и общественно-политической деятельности председателя Черниговской губернской земской управы в 1901 - 1906 и 1917 - 1918 гг. А. Свечина. Определены основные этапы жизненного пути, дана характеристика его работы в губернском земстве и общественно-политической деятельности в начале ХХ в. The article is devoted to the analysis of O.Svechin's life, and social activity. Oleksij Svechin was a zemstvo-councilor and the chief of Chernihiv government zemstvo executive committee in 1901 - 1906 and 1917 - 1918. The main milestones of his course of his life have been defined. His activities as a member of Chernihiv government zemstvo at the beginning of 20th century and his work on leading position of province zemstvo government have been investigated.